Teaching Honesty and Improving Democracy in the Post‐Truth Era. Issue 1 (15th March 2023) - Stitzlein, Sarah
Abstract: In this paper, Sarah Stitzlein considers the consequences of honesty on our democracy, especially for citizens' ability to engage in civic inquiry together as they face shared problems. Honesty is a key component of a well‐functioning democracy; it develops trust and fosters the sorts of relationships among citizens that enable civic dialogue and reasoning. Post‐truth attitudes and truth decay pose serious obstacles to good civic reasoning as citizens struggle to draw clear distinctions between fact and opinion, weigh personal beliefs and emotions over facts, and increasingly distrust traditionally respected sources of information. Stitzlein employs a Deweyan pragmatist account of truth and a distinctly social account of democracy to build a case for foregrounding honesty in the development of citizens. She describes how schools can employ communities of inquiry to cultivate habits of honesty within citizenship education. She explains how a better democracy — one grounded in a wider understanding of social life and relationships — might head off the temptation to be dishonest for self‐serving reasons, focusing on how dishonesty jeopardizes our relationships to each other as citizens and our ability to engage in civic reasoning together to fulfill shared goals.